Use of national early warning score in emergency department among adults with febrile illness to predict admission, ICU admission and mortality - Maharjan, Rony; Shrestha, John; Mangal Joshi, Dipesh; House, Darlene Rose (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: National Early Warning Score (NEWS) is now a well-known tool used by many countries in the Emergency Department (ED) to predict the severity of the disease and intervene on time. The main aim of this study is to check the sensitivity of the national early warning score in finding sick cases that require possible ICU admission and possible mortality cases.Method: A cross-sectional study was conducted in the Emergency Department at Patan Academy of Health Science (PAHS) over one year. The inclusion criteria of the data for this study were age>15 years old and patients with febrile illness (temperature ≥38°C) presenting to the Emergency Department. Data was analyzed using Microsoft Excel and Statistical Package for Social Sciences version 28.0.Result: Predictive sensitivity of medical severity of overall cases was observed. The National Early Warning Score was highly sensitive in foreseeing and finding severe cases that required immediate ICU admission (0.74) or cases with high mortality (0. 94).Conclusion: As per the findings from the study, introducing a National Early Warning Score tool for screening at the Emergency Department in Nepal can be very helpful in identification of deteriorating cases which need ICU admission or risk of mortality.